2013
DOI: 10.19030/iber.v12i11.8176
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Aid, Domestic Savings, And Economic Growth In South Asia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Therefore, foreign aid has positive impacts only in those economies that have good fiscal, monetary and trade policies, Burnside and Dollar (2000), which means that good economic policy pre-requested for aid effectiveness, Murshed and Khanaum (2014). Basnet (2013) examined the role of foreign aid on savings and economic growth in South Asian countries by utilizing a simultaneous equation system. He found that foreign aid enhances economic growth in five South Asian countries and foreign aid adversely influences Business andEconomic Research ISSN 2162-4860 2016, Vol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, foreign aid has positive impacts only in those economies that have good fiscal, monetary and trade policies, Burnside and Dollar (2000), which means that good economic policy pre-requested for aid effectiveness, Murshed and Khanaum (2014). Basnet (2013) examined the role of foreign aid on savings and economic growth in South Asian countries by utilizing a simultaneous equation system. He found that foreign aid enhances economic growth in five South Asian countries and foreign aid adversely influences Business andEconomic Research ISSN 2162-4860 2016, Vol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The government expenditure is an important explanatory variable of economic growth, furthermore, it's a source of economic growth as in Barro model, Barro, (1990) ;Ferreira & Simoes (2013); Adams, & Atsu, (2014); Collier &Dollar, (2002) andBasnet, (2013) . The government expenditure is expected to affect growth positively.…”
Section: Government Consumptionmentioning
confidence: 99%
“…Equation 2 Equation 3 International Journal of Regional Development ISSN 2373-9851 2016 Where: GDPc is GDP per capita, which is GDP in constant prices, this is the proxy of economic growth, John et al (2015), Basnet, (2013 and Ekanayake, & Chatrna, (2010). ODA is total official development flow in constant prices.…”
Section: Equationmentioning
confidence: 99%
“…Basnet (2013) examined the relationship on foreign aid, domestic savings and economic growth in South Asia using simultaneous equation system. The result indicated that aid has positive and significant effect on the growth rates of five nations studied during 1960 to 2008.…”
Section: Aids and Grants And Domestic Savingsmentioning
confidence: 99%